Korean Beauty Product Branding Trough Men: A Prestige Fulfillment For Fans - Ananda Wahidah; Siti Nurbayani K; Anwar Soleh Purba; Tutin Aryanti; Imam Malik (Yayasan Ilomata, 2023)
The visual beauty of entertainment actors is the main attraction for Korean popular culture products, especially beauty trends. Korean wave through beauty products offers a new discourse that beauty is not only absolute for the female but also represented through the male body. This is interesting to research because the preference for consumption patterns of aesthetic culture among Korean fans is not only for women, male fans are also objects of the Korean beauty product market. Interviews were conducted with Korean fans in Bandung, who are members of the Hansamo community and members of the cover dance by face-to-face. The results showed that South Korea successfully marketed beauty products through the perfect visual quality of Korean celebrities, instant branding, pop-up stores with attractive themes, and the provision of free testers. Korean Wave succeeded in utilizing the desire of Korean fans to consume Korean beauty products to fulfill their prestige in achieving the perfect face, fashion (style), and appearance like their idol.